Advances in HDR Display Technology for Cinema Applications, Including Light‐Steering Projection. Issue 3 (3rd May 2019) - Ballestad, Anders; Boitard, Ronan; Damberg, Gerwin; Stojmenovik, Goran
Abstract: Cinematic display solutions are catching up with consumer display technologies' capabilities in both brightness and contrast. However, a mainstream rollout of HDR in cinema requires a high‐performing and cost‐effective solution. In this article, the first of a two‐part series, the authors review solutions being developed and performance specifications suggested for HDR on the big screen.